Analisis Yuridis Peraturan Pemerintah Pengganti Undang-Undang No. 1 Tahun 2020 Tentang Kebijakan Keuangan Covid-19 Terhadap Penggunaan Anggaran Di Masa Pandemi - Fatma Reza Zubarita (Lex Renaissance, 2022)
The Covid-19 pandemic has impacted the economic sector. To that end, the Government issued Perppu No. 1 of 2020 on the Covid-19 Financial Policy as the implementation of fiscal policy efforts. However, there remain obstacles in the form of a large state deficit. The author formulates two legal issues, namely, first, how is the juridical analysis of Perppu No. 1 of 2020 on the Covid-19 Financial Policy on the use of the budget during the Covid-19 pandemic?; second, what is the government's financing strategy to overcome the deficit during the COVID-19 pandemic through fiscal policy? The research method used is a normative juridical method with a statutory approach with secondary data collection, covering primary, secondary, and tertiary legal materials, and compiled descriptively. The results of this study conclude, first, the juridical analysis of the issuance of Perppu No. 1 of 2020 on the Covid-19 Financial Policy on the use of budgets during the pandemic can lead to potential abuse of authority by the government on the state budget in handling Covid-19; second, fiscal policy by the government as a strategic effort to overcome the state deficit by optimizing revenue and realization of state expenditures to maintain the growth and stability of the Indonesian economy.Key Words: Enactment of perppu; budget policy implementation; fiscal policy AbstrakPandemi Covid-19 telah menimbulkan dampak pada sektor ekonomi. Untuk itu, Pemerintah menerbitkan Perppu No. 1 Tahun 2020 tentang Kebijakan Keuangan Covid-19 sebagai penerapan upaya kebijakan fiskal. Namun, masih mengalami kendala berupa defisit negara yang besar. Penulis merumuskan dua permasalahan hukum yaitu, pertama, bagaimana analisis yuridis Perppu No. 1 Tahun 2020 tentang Kebijakan Keuangan Covid-19 terhadap penggunaan anggaran di masa pandemi covid-19?; kedua, bagaimana strategi pembiayaan pemerintah untuk mengatasi defisit di masa pandemi covid-19 melalui kebijakan fiskal? Metode penelitian yang digunakan adalah metode yuridis normatif dengan pendekatan peraturan perundang-undangan dengan pengumpulan data sekunder, meliputi bahan hukum primer, sekunder, dan tersier, serta disusun secara deskriptif. Hasil penelitian ini menyimpulkan, pertama, analisis yuridis penerbitan Perppu No. 1 Tahun 2020 tentang Kebijakan Keuangan Covid-19 terhadap penggunaan anggaran di masa pandemi bisa menimbulkan potensi penyelewenangan kewenangan yang dilakukan oleh pemerintah terhadap anggaran negara dalam penangan covid-19; kedua, kebijakan fiskal oleh pemerintah sebagai upaya strategis mengatasi defisit negara dengan optimalisasi pendapatan dan realisasi pengeluaran negara untuk menjaga pertumbuhan dan kestabilan perekonomian Indonesia.Kata-kata Kunci: Penerbitan perppu; implementasi kebijakan anggaran; kebijakan fiskal